2013
DOI: 10.1111/bjd.12151
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing identifies a novel missense mutation in EDAR causing autosomal recessive hypohidrotic ectodermal dysplasia with bilateral amastia and palmoplantar hyperkeratosis

Abstract: References1 Imperial R, Helwig EB. Angiokeratoma. A clinicopathological study. Arch Dermatol 1967; 95:166-75. 2 Schiller PI, Itin PH. Angiokeratomas: an update. Dermatology 1996; 193:275-82. 3 Anderson W. A case of angiokeratoma. Br J Dermatol 1898; 10:113-17. 4 Holmes RC, Fensom AH, McKee P et al. Angiokeratoma corporis diffusum in a patient with normal enzyme activities. J Am Acad Dermatol 1984; 10:384-7. 5 Vargas-Díez E, Chabás A, Coll MJ et al. Angiokeratoma corporis diffusum in a Spanish patient with aspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 11 publications
2
9
0
2
Order By: Relevance
“…However, recently identified EDAR mutations demonstrate that pathogenic variants result in variable phenotypes with mild-tosevere clinical manifestations. 5 We report a novel mutation in the EDAR gene in an Italian family with autosomal dominant HED that supports emerging evidence for a genoytype-phenotype correlation. 5 The clinical, genetic and functional studies were conducted according to the Helsinki declaration and written informed consent was obtained from all participating family members; including consent to publish data and clinical images.…”
Section: Identification Of a Novel Frameshift Mutation In The Edar Gesupporting
confidence: 78%
See 1 more Smart Citation
“…However, recently identified EDAR mutations demonstrate that pathogenic variants result in variable phenotypes with mild-tosevere clinical manifestations. 5 We report a novel mutation in the EDAR gene in an Italian family with autosomal dominant HED that supports emerging evidence for a genoytype-phenotype correlation. 5 The clinical, genetic and functional studies were conducted according to the Helsinki declaration and written informed consent was obtained from all participating family members; including consent to publish data and clinical images.…”
Section: Identification Of a Novel Frameshift Mutation In The Edar Gesupporting
confidence: 78%
“…5 We report a novel mutation in the EDAR gene in an Italian family with autosomal dominant HED that supports emerging evidence for a genoytype-phenotype correlation. 5 The clinical, genetic and functional studies were conducted according to the Helsinki declaration and written informed consent was obtained from all participating family members; including consent to publish data and clinical images. Three members of the family were available for detailed clinical investigation (V:5; IV:7; IV:5), and four underwent molecular genetic analysis (V:5; IV:7; IV:5; III:2) ( Fig.…”
Section: Identification Of a Novel Frameshift Mutation In The Edar Gesupporting
confidence: 78%
“…The observation of the scalp abnormality in Patient 2 suggests a potential mechanistic connection between KMT2D and KCTD1 , which both code for proteins involved in transcriptional regulation. Additional genes that are associated with abnormal breast development include: (a) TBX3 , which causes Ulnar‐Mammary syndrome (MIM 181450) (M. Bamshad et al, ); (b) TP63 which causes multiple developmental disorders (M. J. Bamshad, ; Rinne, Hamel, van Bokhoven, & Brunner, ); (c) EDA , which causes X‐Linked Hypohidrotic Ectodermal Dysplasia (XLHED) (MIM 305100) (Wahlbuhl‐Becker, Faschingbauer, Beckmann, & Schneider, ); (d) EDAR , which causes autosomal recessive hypohidrotic ectodermal dysplasia (MIM 224900) (Haghighi et al, ); and (e) Figure , which causes Yunis–Varon syndrome (MIM 216340) (Campeau et al, ). Two families with variants that disrupt PTPRF have been reported to have athelia (MIM 616001) (Ausavarat et al, ; Borck et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, Sanger sequencing and multiplex ligation-dependent probe amplification have been commonly used for EDA mutation discovery in both research and clinical studies (Lexner et al, 2008). Recently, whole-exome sequencing has been reported to be an economical and rapid tool for genetic diagnosis, and it has been used to diagnose types of disorders similar to ED (Haghighi et al, 2013). In this study, we performed whole-exome sequencing to screen ED-associated genes in a boy affected with HED, and identified that an EDA (G299D) mutation might be the primary cause of the disorder in this patient.…”
Section: Discussionmentioning
confidence: 99%